Case-Based Learning on Islamic Religious Education Subjects at SMA Negeri 40 Jakarta - Marno; Basuki Wibawa; Popi Puadah (CV ODIS, 2022)
This research aims to describe and prove the feasibility of the results and effectiveness of the development of Case-based Learning (CBL) Models in Islamic Religious Education subjects at SMA Negeri 40 Jakarta. Conceptually, CBL through Islamic education can be described as follows: 1). Development of the PAI learning model, 2). PAI learning model, 3). Analysis of learning variables in the CBL PAI model: a) Analysis of PAI learning objectives, b) Characteristics of PA and subject matter according to the CBL model, c) Analysis of learning constraints, d) Analysis of teacher competence in the CBL model, e) Analysis of student characteristics, f) Analysis of facilities and infrastructure, g) Determining learning objectives and learning content using the CBL model, h) Establishing strategies for organizing learning content, i) Determining strategies for delivering learning content, j) Establishing learning management strategies, k) Developing learning assessment procedures. Furthermore, the procedural development of the CBL model through Islamic education is carried out in the following stages: 1). Identify learning objectives, 2). Learning analysis, 3). Analyzing students and context, 4). Write performance goals, 5). Developing assessment instruments, 6). Developing learning strategies, 7). Develop and select teaching materials, 8). Designing and conducting a formative evaluation of learning, 9). Identify learning objectives, 10). Design and conduct a summative evaluation. The method used is research and development (R&D) with a case study approach. The research and development stage of the CBL model through Islamic religious education refers to the incorporation of Dick and Carey’s version of the R&D model (Gall, and Borg, 2007) with Timothy Kirk Nelson's version of the CBL model with the following stages: 1). Identification and data collection, 2). Analyzing Learning, 3). Analyzing Student Initial Behavior, 4). Developing Test Points, 5). Formulating Performance Goals, 6). Developing Learning Strategies, 7). Developing and Selecting Learning Materials, 8). Designing and Implementing Formative Evaluations, 9). Revising the Learning Program, 10). Designing and Developing Summative Evaluations. The population in this study was 76 respondents. Data sources are taken from lecturers, principals, teachers, and also students. The data collection methods used are interviews, observations, questionnaires, documentation, expert validation, and tests. The data analysis methods used are qualitative and quantitative with the SPSS 26 statistical analysis program. The results showed that there was an improvement in the learning outcomes of students who had used PAI modules with